Akuntabilitas Pidana di Era Penyalahgunaan Kecerdasan Buatan ditinjau dari Asas Legalitas - Ginting, Yuni (The Prosecutor Law Review, 2025)
The development of artificial intelligence (AI) presents new challenges in criminal law, especially in determining the subject responsible for actions arising from autonomous systems. The phenomenon of AI misuse raises issues regarding the application of the principle of legality, which demands clarity on the perpetrator, the act, and the sanction. This research aims to examine how the principle of legality can address the problem of criminal accountability in the digital era. The method used is normative juridical with a statutory and conceptual approach, through analysis of national regulations and international legal principles related to criminal responsibility. The results show that the principle of legality remains relevant but requires reinterpretation so that it can cover acts mediated by technology. It is concluded that strengthening legal norms and responsibility based on human control is necessary to maintain legal certainty and prevent a vacuum of accountability in the age of artificial intelligence.